Costs of elephant crop depredation exceed the benefits of trophy hunting in a community‐based conservation area of Namibia. Issue 1 (23rd December 2020) - Drake, Michael D.; Salerno, Jonathan; Langendorf, Ryan E.; Cassidy, Lin; Gaughan, Andrea E.; Stevens, Forrest R.; Pricope, Narcisa G.; Hartter, Joel
Abstract: The Kazavango‐Zambezi Transfrontier Conservation Area is home to the largest remaining elephant population in Africa but is also the site of high levels of human‐elephant conflict through crop depredation. Offsetting the costs of coexisting with elephants in this area is critical to incentivizing elephant conservation within community‐based conservation (CBC) areas, and trophy hunting has long been touted as a method for generating revenue for communities from wildlife. However, the idea that sustainable elephant hunting can offset the costs of crop depredation remains largely untested. We combined household survey data, financial records, and elephant population data to compare the potential benefits of sustainable hunting with the costs of crop depredation in a CBC area in northeastern Namibia. We determined that sustainable trophy hunting only returns ~30% of the value of crops lost to the community and cannot alone offset the current costs of coexistence with elephants. As core institutions supporting the practice of conservation, CBC efforts must promote community management capacity to combine multiple wildlife‐based income streams and build partnerships at multiple scales of governance to address the challenges of elephant management.